(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
ABSTRACT Context: Medical residency is the main form of practical specialization after graduation. Governed by specific legislation rather than the CLT, it raises debates about its labor nature since residents perform professional duties similar to employed physicians but are legally treated as trainees. Objective: This paper critically examines the convergences and divergences between the legal regime of medical residency and labor law, explaining why residents are not considered employees and assessing the coherence and effectiveness of this legal distinction. Method: A bibliographic and doctrinal review was conducted on Law No. 6.932/1981 and the CLT, alongside jurisprudential analysis and empirical studies on residents’ working and learning conditions in Brazilian hospitals. Results: The study found that, although residency grants rights similar to CLT employees—such as leave and rest—its formative nature prevails. However, excessive workloads and legal noncompliance reveal a gap between the law and the real situation of residents. Conclusions: The current legal framework fails to protect residents, who face heavy workloads and responsibilities inconsistent with an educational program. Revising the law to expand rights and align learning with fair labor conditions is necessary. Keywords: Medical residency. Labor law. Employment relationship.